Study on Factors Affecting Household Income from Rubber Production in Xaybouly District, Savannakhet Province - VONGKHASEUM, Bounphan; KHAMSOMBATH, Phouvisakha; SUPHANTHALAD, Minalin; TOUNMANYSONE, Thongsa (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purpose of this study is to investigate rubber production as a household economic activity and to examine the factors influencing household income from rubber production in Xaybouly District, Savannakhet Province. Data were collected from a random sample of 254 households using structured questionnaires. Descriptive statistics and linear regression models were employed, and multivariate analysis was conducted using STATA software to estimate the coefficients reflecting the relationships between the dependent and independent variables. The results indicate that 56.3% of households in Xaybouly District produce 100 tons of rubber or less annually. Approximately 55.91% of producers sell around 100,000 kilograms of rubber, with 97.64% of households selling at a price of 17,000 kip per kilogram. Annual sales revenue for 39.37% of households is approximately 1,000,000,000 kip. The annual production cost for 57.48% of households is about 100,000,000 kip, and the total cost of rubber planting falls within the same range for 51.97% of households. Findings from the Ordinary Least Squares (OLS) regression model reveal four key factors that significantly affect household income from rubber production: (i) the experience of the household head, (ii) the area allocated for rubber cultivation, (iii) expenditure on rubber cultivation, and (iv) the rubber variety planted. These factors have a positive influence on income generation. In contrast, variables such as gender, education level, number of household workers, rubber price, use of chemical fertilizers, use of pesticides, and distance from the farm to the market were not statistically significant and, therefore, do not have a measurable effect on household income from rubber production.